PRACTICES OF THE QUALITY OF GOVERNMENT IN IMMIGRATION CONTROL AT INTERNATIONAL AIRPORTS - Arifin, Ridwan; Bawono, Sri Kuncoro (PEOPLE: International Journal of Social Sciences, 2019)
The quality of government by Rothstein and Teorell refers to the term of impartiality in the exercise of public authority which comprises an equal conduct to public administration, public choice, multiculturalism, and feminism. This qualitative research with multidisciplinary approach examines the quality of government in immigration control at airports in Indonesia from its perspectives, principles, and practices. The result shows it has not considered the quality of government and has not designed a framework or model of the quality of government in immigration control at airports. We propose the quality of government utilizes principles of the moral law of public authority which refers to Kantianism constructivism, formalism, positivism, and rule of law. The perspectives on the quality of government should encompass human rights, sovereignty, border integrity, international law aspects, and information systems. In practices of immigration control, the quality of government shall generate positive impacts on economy, socio-culture, politics, cooperation, and national security of a country.